P Perlawanan Laki-laki terhadap Toxic Masculinity dalam Serial Sugar Daddy - Maulida, Aprilia; Ahmadi, Anas (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This study aims to reveal the representation of toxic masculinity and the resistance of the character Derry against traditional masculine constructions in the series Sugar Daddy. The approach used is qualitative with a narrative content analysis method. Data were collected through observation of scenes and dialogues in the series, then analyzed using Kupers' (2005) theory of toxic masculinity. The findings show that Derry initially embodies toxic masculinity characterized by emotional repression, self-isolation, and refusal of help. However, through counseling processes and social relationships, Derry begins to exhibit a transformation toward a new form of masculinity that is empathetic, reflective, and emotionally open. This transformation demonstrates that traumatic experiences can serve as a turning point for men to reject social constructs that suppress emotional expression. The series also highlights interpersonal relationship dynamics as essential media in the healing and identity transformation process. Furthermore, this series conveys educational messages about the importance of emotional balance and gender equality in modern society. Thus, Sugar Daddy becomes a significant representation of male resistance against toxic masculinity and the transformation of masculine identity in a more inclusive and humanistic modern era. This study contributes to literary and gender studies by highlighting shifts in masculine values within Indonesian popular culture.